Dair approach in 7 infected total hip arthroplasties: our experience and current concepts of the literature - Schiavi, Paolo; Pogliacomi, Francesco; Calderazzi, Filippo; Domenichini, Marco; Ceccarelli, Francesco; Vaienti, Enrico (Acta Biomedica Atenei Parmensis, 2022)
Abstract. Introduction: Periprosthetic joint infection (PJI) is one of the most challenging complications following total hip arthroplasty. In early infection, within four to twelve weeks from surgery, debridement, antibiotics and implant retention (DAIR) can be the initial treatment. The aim of this study is to report our case series and review current concepts reported in the literature about this topic. Materials and Methods: This was an observational cohort study that included 7 patients managed with DAIR for PJI following primary total hip replacement (THR) between 2014 and 2020. Inclusion criteria were a primary THR, direct anterior or lateral approach, DAIR procedure, and PJI. Exclusion criteria were a PJI following a revision total hip replacement or hemiarthroplasty, posterolateral approach, 1-stage revision, 2-stage revision, and Girdlestone procedure without prior DAIR. For each patient demographic characteristics, laboratory values, microorganisms involved, antibiotic therapy and outcome at one-year follow-up were registered. Results: The mean duration between THR and DAIR was 19 days. In all cases only one DAIR procedure was performed. Most infections were caused by Staphylococcus aureus (4 cases) [one methicillin resistant (MRSA)]. The other infections were caused by Streptococcus agalactiae, Staphylococcus coagulase negative and Escherichia coli. At the final follow-up, the procedure was considered as successful in 6 out of 7 patients (85%). The one with unsuccessful outcome underwent to a two-stage revision. Discussion: Our results were comparable with those of a recent systematic review of the literature. Factors that have been postulated to influence the outcome of DAIR in the management of PJIs include the timing and numbers of debridement, the exchange of components, the responsible microorganism and the duration of antibiotic treatment. In conclusion, the outcomes following DAIR are better as the indications are refined and risk factors identified. PJI prevention remains the key but the current literature still lacks well documented and effective PJI prevention protocols. (www.actabiomedica.it)